Identification of Infrastructure and Community Involvement Towards Improving the Quality of Roads in Beakang Padang District, Batam City - Oktama, Muda Andrian; Sidabutar, Yuanita FD (Borong Newinera Publisher, 2024)
This research aims to identify the condition of road infrastructure, measure the level of community participation in efforts to improve the quality of environmental roads, and evaluate the impact on the aesthetics of the area in Behind Padang District, Batam City. Good infrastructure and active community participation are very important in creating a comfortable and aesthetic environment, which in turn can improve the quality of life and welfare of the community. The research method used is a descriptive method with a qualitative approach, which allows for in-depth data collection through field observations, in-depth interviews and documentation studies. The data obtained was analyzed qualitatively using a data reduction approach, data presentation and drawing conclusions. Field observations show that the physical condition of roads in the Rear Padang District varies greatly. Some main roads are in good condition with smooth asphalt surfaces, but many neighborhood roads are damaged, potholed and poorly maintained. This condition is exacerbated by supporting infrastructure such as drainage channels and street lighting which is still very limited in some areas. This deficiency has a negative impact on the comfort and safety of road users and reduces the aesthetics of the environment. This research found that improving road infrastructure and increasing community participation had a significant impact on the aesthetics of the area. Well-improved roads and well-organized neighborhoods create a more pleasant atmosphere and increase resident satisfaction. Active community participation in infrastructure planning also increases the sense of ownership and responsibility.